Pathophysiological Changes in Purulent-Necrotic Foot Lesions in Diabetes Mellitus and Optimization of Complex Treatment: An Experimental Study - Rafiqovich, Zokhirov Adkhamjon (Journal of Science in Medicine and Life, 2025)
Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia. In 2019, 463 million people worldwide were diagnosed with diabetes. According to forecasts, the number of people with DM is expected to reach 578 million by 2030 and 700 million by 2045. The increasing prevalence of diabetes has led to a rise in diabetic wound cases, significantly escalating the medical costs associated with wound treatment globally.